Fibroblast growth factor 18 exerts anti-osteoarthritic effects through PI3K-AKT signaling and mitochondrial fusion and fission. (January 2019) - Yao, Xudong; zhang, Jiaming; Jing, Xingzhi; Ye, Yaping; Guo, Jiachao; Sun, Kai; Guo, Fengjing
Graphical abstract: Abstract: Osteoarthritis (OA) is a degenerative disease characterized by progressive loss of cartilage, osteophyte formation and subchondral bone sclerosis. Although some animal experiments have reported that fibroblast growth factor 18 (FGF18) attenuates cartilage degradation, the effect of FGF18 on chondrocytes and its underlying mechanism at the cellular level remain largely unknown. In this study, we found that an intra-articular injection of FGF18 attenuates cartilage degradation, increases Collagen II deposition and suppresses matrix metallopeptidase 13 (MMP13) expression in rat post-traumatic osteoarthritis (PTOA). At the cellular level, FGF18 promotes chondrocyte proliferation through PI3K-AKT signaling and migration through PI3K signaling. We found that FGF18 attenuates IL-1β-induced apoptosis, restores mitochondrial function and reduces Reactive Oxygen Species (ROS) production through PI3K-AKT signaling. Moreover, the mitochondrial fusion and fission of chondrocytes were enhanced by a short duration of treatment (within 24 h) of IL-1β and suppressed by prolonged treatment (48 h). FGF18 significantly enhances the mitochondrial fusion and fission, restoring mitochondrial function and morphology, and reduces ROS production. We also found that the FGFR1/FGFR3 ratio, which might contribute to the progression of osteoarthritis, was upregulated by IL-1β and downregulated by FGF18. To the best of our knowledge, our data demonstrated the anti-osteoarthritic effect of FGF18 at the cellular level for the first time and suggested that PI3K-AKT signaling and mitochondrial fusion and fission might play critical roles during the process. Our study proved that FGF18 might be a promising drug for the treatment of early stage osteoarthritis and is worth further study.